Engineered biomimetic nanovesicles-laden multifunctional hydrogel enhances targeted therapy of diabetic wound - Shuoyuan Liu; Gui Wan; Tao Jiang; Chengqi Yan; Guoyong Jiang; Maojie Zhang; Kaituo Xiang; Chi Zhang; Xuejiao Xiang; Huayuan Zhao; Chengcheng Li; Zhichao Ruan; et al. (Materials Today Bio)
Angiogenesis is essential for diabetic wound healing. Endothelial progenitor cell-derived extracellular vesicles (EPC-EVs) are known to promote wound healing by enhancing angiogenesis, while the low yield and lack of effective targeting strategies limit their therapeutic efficacy. Here, the biomimetic nanovesicles (NVs) prepared from EPC (EPC-NV) through an extrusion approach were reported, which functioned as EV mimetics to deliver contents from EPC to the wound. Besides, the cRGD peptide was coupled to the surface of EPC-NV (mEPC-NV) to achieve active endothelial cells (ECs)-targeting. Furthermore, we developed a dual hydrogel network by combining Fe3+@ Protocatechualdehyde (PA) complex-modified Acellular Dermal Matrix (ADM) with light-cured gelatin (GelMA), to enrich and sustainably release mEPC-NV. The hydrogel system with antioxidant and antibacterial properties also made up for the deficiency of mEPC-NV, reducing reactive oxygen species (ROS) and inhibiting infection in diabetic wound. Taken together, this study established a novel bioactive delivery system with angiogenesis, antioxidant and antibacterial activities, which might be a promising strategy for the treatment of diabetic wound.